2017
DOI: 10.1111/jpy.12502
|View full text |Cite
|
Sign up to set email alerts
|

A metabarcoding comparison of windward and leeward airborne algal diversity across the Ko‘olau mountain range on the island of O'ahu, Hawai‘i1

Abstract: Airborne algae from sites on the windward (n = 3) and leeward (n = 3) sides of the Ko'olau Mountain range of O'ahu, Hawai'i, were sampled for a 16 d period during January and February 2015 using passive collection devices and were characterized using Illumina MiSeq sequencing of the universal plastid amplicon marker. Amplicons were assigned to 3,023 operational taxonomic units (OTUs), which included 1,189 cyanobacteria, 1,009 heterotrophic bacteria, and 304 Eukaryota (of which 284 were algae and land plants). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Moreover, we found no evidence for dispersal limitation in other common acidophilic microalgae besides ESU34 (G. maxima OTU1) and ESU35 (G. maxima OTU2). Indeed, dispersal by air or birds is reportedly common in different groups of microalgae (Proctor 1959, Sherwood et al 2017. Consistent with this observation, we found two acidophilic green algae (ESU7 and ESU11) in some air dust samples that we collected as part of our fieldwork (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, we found no evidence for dispersal limitation in other common acidophilic microalgae besides ESU34 (G. maxima OTU1) and ESU35 (G. maxima OTU2). Indeed, dispersal by air or birds is reportedly common in different groups of microalgae (Proctor 1959, Sherwood et al 2017. Consistent with this observation, we found two acidophilic green algae (ESU7 and ESU11) in some air dust samples that we collected as part of our fieldwork (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, dispersal by air or birds is reportedly common in different groups of microalgae (Proctor , Sherwood et al. ). Consistent with this observation, we found two acidophilic green algae (ESU7 and ESU11) in some air dust samples that we collected as part of our fieldwork (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past twenty years, phylogenetic analyses have demonstrated that an approach based on morphological determination alone is somewhat artificial for most of the microalgal genera and should be revised 25,26 . Several studies recently estimated the diversity of indigenous photosynthetic microbial communities in various environments using metabarcoding coupled with high-throughput sequencing (HTS) 3,[27][28][29][30][31][32][33][34] . A range of molecular markers has been used to describe cyanobacterial and photosynthetic microeukaryote diversity with varying degrees of resolution (e.g., 16S/18S/23S rRNA, tufA, psbA, rbcL, ITS) 32,[35][36][37][38][39] .…”
mentioning
confidence: 99%
“…Moreover, UPA has a length (~410 bp) suitable for HTS Technologies 43 , such as Illumina 45 . UPA can also be used in addition to other markers to obtain a comprehensive overview of microbial diversity 31,37,39,46 .…”
mentioning
confidence: 99%
See 1 more Smart Citation